Performance evaluation of multi-cloud compared to the single-cloud under varying firewall conditions. Issue 1 (1st January 2018) - Yeasmin, Mahbuba; Akter, Nahida; Kabir, Mohammed Humayun; Hossain, Javed
Abstract: The main purpose of this paper is to evaluate the network performances of multi-cloud compared to the single cloud under several firewall scenarios. Riverbed Modeler is used as the simulation tool in this project, and several projects are formed in this context. The projects consist of single cloud with single server, single cloud with multiple servers, multiple clouds with single server, and multiple clouds with multiple servers. In the first project, there are two scenarios: first, no firewall security across the cloud; second, the actual firewall implementation and this particular firewall allows all the required traffic. The second, third, and fourth projects were simulated with no security across the cloud, actual firewall security, and the third scenario deals with the firewall implementation that discards the web traffic. Database, web, e-mail, and file transfer applications are used as the required applications across the cloud to generate the traffic and the firewalls will act on these applications. The simulation results in the improvement of high performance of multiple clouds with firewall reducing the load request time, average response time, and Ethernet delay.